Black imagination and the Middle Passage - Diedrich, Maria; Gates, Henry Louis, Jr; Pedersen, Carl (W.E.B. Du Bois Institute (Series), 1999)
This volume of essays examines the forced dispossession caused by the Middle Passage. The book analyzes the texts, religious rites, economic exchanges, dance, and music it elicited, both on the transatlantic journey and on the American continent. The totality of this collection establishes a broad topographical and temporal context for the Passage that extends from the interior of Africa across the Atlantic and to the interior of the Americas, and from the beginning of the Passage to the present day.